“Memory and Desire”: T.S. Eliot, Reaction, Nostalgia, and Poetic Reserve in The Waste Land - Philippe Birgy (Association Française d'Etudes Américaines, 2019)
This paper explores the concept of reaction in relation to T.S. Eliot’s poetry, unfolding its various implications as psychological motivation, temporal perception and political vision. It considers the possible relevance such factors might have had on the composition of The Waste Land. It first reviews the state of the art and recasts the different critical positions in a historical and cultural perspective, then reflects on what passes off as the fundamental rift between the commentators of Eliot, depending on whether they prescribe a close stylistic scrutiny of Eliot’s poem or a general contextualisation as the premise of their literary assessment. On the face of it, the dispute revolves around the question of the author’s responsibility and accountability for his work and the positions held by the contestants are liable to become entrenched, sometimes to the point of preventing the actual confrontation of critical insights. Our contention will be that a simplification or standardization of the term “reaction” often obscures the fact that modernism is not simply contested or “in debate” but that modernism is the debate itself—in other words, that modernism is constitutively and structurally problematic. Modernism as manifested or endorsed by Eliot in the form of a writing programme consists precisely in that exposure to the conflict inherent in poetic practice, in the direct confrontation to insoluble dilemmas. These tensions, I argue, are located in the text itself and account for the strange thrust of its poetic move that withdraws instantly what it has just pushed forward.